(untitled) (Research, Society and Development, 2021)
This is a research carried out with a group of elderly people who actively participate in an Elderly Living Center located in the East Zone of São Paulo. The objective was to verify the association between the levels of physical activity and variables related both to the multidimensionality of health in the elderly and to the degree of perceived stress. It was also investigated which of the studied variables influenced the levels of physical activity found in this group. 57 elderly people participated, a majority of women, widowed or married, with low education levels, an average age 74.7 years, able to perform basic and instrumental activities of daily living independently, without risk of falling or of dementia. These elders, in general, self-perceived their health as good or excellent, being physically active. A statistically significant association was found between the presence of depressive symptoms and high levels of perceived stress, noting that irregularly active elderly people had more depressive symptoms and worse self-perceived health. For each depressive symptom measured by the Yesavage geriatric depression scale, there was an 11% decrease in the probability of the elderly in the group being physically active.